História comportamental em sujeitos humanos: efeitos da história de reforço em esquemas de DRL ou FR sobre o responder em esquema de FI e possíveis implicações da resposta de consumação nesses esquemas - Teixeira, Gustavo (2006)
The present study researched the effects of the reinforcement history under DRL or FR schedules upon the response under FI schedule and the possible implications of the consummatory response in these schedules. Twelve university students from different courses, except from the Psychology school, took part in this research. The subjects were set in 4 groups and submitted to six sessions with 40 reinforcements each. Members of 2 groups were initially exposed to a FR 40 and the members of the other two groups to a DRL 20-sec. Later on, all participants were exposed to three sessions of FI 10- sec. One consummatory response was made a requirement in the six sessions only for the participants of one of the two groups exposed to a FR 40 and for the participants of one of the two groups exposed to DRL 20- sec. The subjects presenting a history of reinforcement under FR (with or without a consummatory response) showed a high rate response standard and relatively constant during the third session exposed to FR 40. All the participants, except one, kept a performance at a high rate of responses when exposed to a FI schedule. Nevertheless, two participants of the FR 40 Group with consummatory response showed a trend to decreasing the response rate throughout the FI exposition sessions, suggesting that the consummatory response may have contributed to the reduction of the response rates. The participants presenting a history of reinforcement in DRL (with and without consummatory response) showed response standard at low and constant rate during the third session of exposition to DRL 20-sec. These participants kept having a performance at low rate of responses when exposed to FI, however the response rate increased remarkably. For those participants members of the Group with no consummatory response, suggesting that the consummatory response may have contributed to the increase of the response rate for the groups with DRL history. Concerning the effects of the history, observing the final performance in FI 10-sec. from the participants with a history of reinforcement under FR and from the participants with a history of reinforcement under DRL, one can see that the general response rate was higher for those participants with a history of FR than for those with a reinforcement history under DRL. These results suggest that the participants behavior along the third session under FI 10-sec. was under the control of the current contingencies and showed effects of the reinforcement history